The Cultural Relation Between Verbal Language and Visual Image In English Textbooks for Junior High School - F, Rizqi Amalia; Warsono, Warsono; Hartono, Rudi (Universitas Negeri Semarang, 2018)
The globalization era makes the student more focus to learn and know the international language and international culture. Therefore, this study wants to investigate how the cultural balance represents in the primary source of the English subject. One of the most important resources for student is Textbooks. This study analyzes English Textbooks at contain cultural dimension. This study focus on the visual and verbal language which contain cultural dimension beside, the assumption that visual language is only the complement of verbal language in a text. Thus, the researcher is interesting to analyze the relation of visual and verbal language. This study investigated combination of image and text in English textbooks for Junior high school. This study use qualitative research in the form of critical discourse analysis to examine picture in textbooks of junior high school within the framework of visual grammar (Gunter Kress & Van Leeuwen, 2006). This study have two instrument that adapted by two experts, those are instrument of cultural dimension by Moran (2001) and Visual grammar by Gunter Kress and Van Leeuwen (2006). The study is aim to know the relation of Verbal and Visual texts.